EBG optimised bandstop filter - Chien, Han Cong. (2012)
The main purpose for this report is to present the design process and fabrication of an Electromagnetic BandGap (EBG) optimized bandstop filter. This report will feature details from the planning stage all the way to fabrication and prototype testing before doing a brief comparison between the desired results and the measured results and the reasons for their difference. As the ideal factors are always compromised with each other, the reasons for design decisions are also discussed. Fabrication of the prototype and measurement results are also compared and discussed.